Cost Efficiency Analysis of the Turkish Banking Industry between 2012 and 2018 - Ahmetrasit, Gizem (2019)
This study examines the cost efficiency of commercial banks in Turkey over the period of 2012-2018 by using stochastic frontier analysis (SFA). The main purpose of this paper is to analyse the cost efficiency of the Turkish banking system over the course of the study period, compare the efficiency of domestic and foreign banks and determine the factors which have an impact on bank efficiency. Following the one-step approach, after the cost efficiency estimates are obtained using the SFA intermediation approach, the Battese and Coelli (1995) model is used to determine several macro-economic and bank-specific factors which directly affect bank efficiency. The analysis is based on a sample of 23 continuously operating commercial banks during 2012-2018 in Turkey. Therefore, a panel dataset is used to determine the cost efficiency of 3 state-owned, 9 privately-owned and 12 foreign banks. Following the intermediation approach, total interest expenses, personnel expenses and other operating expenses are used as inputs. On the other hand, the outputs consist of gross loans, off-balance sheet items and other earning assets. The one-step approach allows to control for macro-economic and bank-specific variables when building the efficient frontier. When examining the determinants of cost efficiency, inflation and GDP growth are used as macro-economic variables whereas bank-specific variables consist of equity to total assets ratio, total loans to total assets ratio and the natural logarithm of total assets. In addition, to examine the effect of ownership on cost efficiency, a dummy variable, which took the value of 1 if banks are foreign and 0 if banks are domestic, is incorporated into the model. In terms of average cost efficiency of the banking sector, although the average level of efficiency fluctuates between 2012 and 2018, the overall trend is declining, indicating an overall decline in cost efficiency. Looking at the efficiency of foreign and domestic banks, foreign banks are found to be more cost efficient than domestic banks over the course of this study. In terms of determinants of cost efficiency, bank size, total loans to total assets ratio and ownership structure have a positive and statistically significant relationship with cost efficiency. Capital adequacy and GDP growth are also found to have a positive impact on cost efficiency, although their relationships are not statistically significant. Despite being statistically insignificant, the relationship between inflation and cost efficiency is found to be positive which contradicts the results of previous studies based on Turkey.